Elicitation of resistance in rice plants against sheath blight with non-conventional chemicals - and A.P. SINHA, R.K. DANTRE, Y.P.S. RATHI (Indian Phytopathology, 2003)
Sheath blight of rice caused by Rhizoctonia solani Kuhn is one of the major production constraints in India. Soil-borne nature of the pathogen and prolonged survival of its sclerotia make the chemical control of this disease a difficult proposition.Breeding for resistance against sheath blight has little scope as no commercial cultivars resistant to this disease is available. Several fungal and bacterial antagonists have been reported against R. solani, but a viable technology for their field application is yet to be perfected. Reports are also in hand indicating induction of resistance in rice plants to R solani by using non-conventional chemicals. Therefore, the present study was executed to find out the possibilities of inducing resistance in susceptible cultivars of rice against R. solani using various non-conventional chemicals.